Blood Na+ /K+ and Cl- Levels of Hyperglycemic Rats Administered with Traditional Herbal Formulations - Alphonsus Ojiako, Okey; Chikezie, Paul Chidoka (Pharmacognosy Communications)
Background/Aim: The present study investigated alterations in blood Na+/K+ and Cl- levels of alloxan-induced hyperglycemic rats (HyGR) administered with single and combinatorial herbal formulations of leaf extracts of Acanthus montanus, Emilia coccinea, Hibiscus rosa sinensis and Asystasia gangetica. Materials and Methods: Serum electrolytes concentrations were measured using the ion selective electrode analyzer. Results: Serum Na+ concentration (SNC) of the untreated HyGR (DIAB group) was significantly (p<0.05) lower than that of the normal control rats (NORM group).However, HyGR administered with single herbal formulations (SHf) exhibited relatively higher SNC than that of the DIAB group (p< 0.05), which was within the range of 133.3±13.6 mMol/L–138.2±15.3 mMol/L; DIAB[Na+]=127.8±12.4 mMol/L. Serum K+ concentration (SKC) of the NORM group was significantly (p<0.05) higher than that of the DIAB group. Serum Cl- concentration (SCC) of the DIAB group was not significantly different (p>0.05) from those treated with SHf. Also, SCC of HyGR treated with triple herbal formulations (THf) was not significantly different (p>0.05) from HyGR treated with double herbal formulations (DHf), THf and quadruple herbal formulation (QHf). SNC exhibited a strong positive correlation with SCC (r=0.703231543). Conversely, SNC versus SKC (r=0.386096385) and SKC versus SCC (r=0.454718488) gave weak positive correlations. Conclusion: The present study showed that the various herbal formulations, in the present form, exhibited varied limited capabilities but substantial potentials to reversing altered blood electrolytes levels of HyGR within the 30- day treatment. Furthermore, definitive blood Na+/K+ and Cl- levels could be of diagnostic relevance in the course of management and treatment of DM.
Keywords: Chloride; Electrolytes; Herbal formulation; Potassium; Sodium